THE EFFECT OF PROBIOTIC ADDITION WITH DIFFERENT DOSES ON GROWTH AND SURVIVAL RATE OF SHRIMP VANAME (Litopenaeus vannamei) - Adliyana, Aimi; Putra, Iskandar; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK The research aims to determine the best probiotic dose to increase the growth rate and survival of vaname shrimp (Litopenaeus vannamei). This research was conducted on March 3 to April 11, 2019, which took place in the Technical Implementation Unit Bantan on Mariman street, Teluk Papal Village, a subdistrict of Bantan, Bengkalis Regency, Riau Province. The method used is the experimental method with a completely randomized design model with 4 levels of treatment and 3 replications. The treatments used are P1: giving probiotics at a dose of 2,5 ml/m3, P2: giving probiotics at a dose of 5 ml/m3, P3: giving probiotics at a dose of 7,5 ml/m3, P4: giving probiotics at a dose of 10 ml/m3. The results of this study indicate that the administration of different doses of probiotics in the maintenance of vannamei shrimp significantly affected absolute weight growth, specific growth rate, feed efficiency, feed conversion ratio and survival of vannamei shrimp (Litopenaeus vannamei). The best treatment is found in P4 which is giving probiotics at a dose of 20 ml/m3 with the results of absolute weight growth of 2.27 g, a specific growth rate of 7.01%, feed efficiency 85.32%, feed conversion ratio of 1.17 and survival of 98.33 %. The range of water quality during the study in all treatments, namely temperatures between 27-310C, salinity 25-33 ppt, pH 6-7, and ammonia 0.33-0.08 mg / L.Keywords: Litopenaeus vanamei, probiotik, survival rate